2010
DOI: 10.3109/10641950903322915
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Chronic Nitric Oxide Synthase Inhibition-Induced Fetal Growth Restriction in the Rat

Abstract: Objective To evaluate the pathophysiology of chronic nitric oxide synthase (NOS) inhibition-induced fetal growth restriction (FGR) in the rat. Methods Timed-pregnant rats received L-NAME (2.5 mg/kg/h) with or without endothelin (ET-1) receptor A (ETA) antagonist from day 14 to 21 of gestation. In separate groups, ETA antagonist and/or L-NAME were discontinued on day 18. On day 21 fetal and placental weights, and maternal and fetal plasma nitrate/nitrite (NOx) were determined. Results L-NAME led to FGR, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…24 It has been reported that NOS inhibition from days 14 to 21 of the 22-day gestation period results in decreased uterine and placental perfusion and decreased fetal and placental growth. 25 Because it has been reported that tumor necrosis factor (TNF)-α, which is induced by repeated endotoxin administrations, activates systemic vascular endothelial cells, 26 the experimental PE model was reproduced by a low-dose endotoxin in this study. Sakawi et al 22 administrated endotoxin at 1, 2 and 10 μg/kg and L-NAME at 3 mg/kg as an experimental PE model and successfully reproduced proteinuria and thrombocytopenia, but not hypertension and intrauterine growth restriction (IUGR), whereas L-NAME administration caused hypertension, IUGR and decreased fetal number.…”
Section: Discussionmentioning
confidence: 97%
“…24 It has been reported that NOS inhibition from days 14 to 21 of the 22-day gestation period results in decreased uterine and placental perfusion and decreased fetal and placental growth. 25 Because it has been reported that tumor necrosis factor (TNF)-α, which is induced by repeated endotoxin administrations, activates systemic vascular endothelial cells, 26 the experimental PE model was reproduced by a low-dose endotoxin in this study. Sakawi et al 22 administrated endotoxin at 1, 2 and 10 μg/kg and L-NAME at 3 mg/kg as an experimental PE model and successfully reproduced proteinuria and thrombocytopenia, but not hypertension and intrauterine growth restriction (IUGR), whereas L-NAME administration caused hypertension, IUGR and decreased fetal number.…”
Section: Discussionmentioning
confidence: 97%
“…This surprising finding could be explained by a possible vasodilator effect of ROS, increasing the uterine blood flow and therefore the birth weight. Actually, nitric oxide is a vasodilator, and chronic nitric oxide synthase inhibition induces fetal growth restriction in the rat (34). Similarly in humans, antioxidant therapy administration in pregnant women at risk of pre-eclampsia resulted in a decrease of mean infant weight, suggesting that ROS have the opposite effect (35).…”
Section: Discussionmentioning
confidence: 98%
“…ET-1 may Life Sciences 91 (2012) 710-715 be the key link between the poorly perfused placenta and the impaired maternal vascular function associated with PE by triggering oxidative stress in the human placenta (Fiore et al, 2005). ET-1 has also been implicated in the pathophysiology of FGR in several animal models as well as in humans (Neerhof et al, 2011;Nezar et al, 2009).…”
Section: Introductionmentioning
confidence: 98%